Financial Disclosure Quality and Capital Market Information Asymmetry Reduction (gjstudies, 2025)
This research investigates the nuanced relationship between the quality of corporate financial disclosures and the reduction of information asymmetry in capital markets, proposing a novel methodological framework that diverges from conventional event-study and regression-based approaches. We introduce a multidimensional, network-based contagion model that conceptualizes information asymmetry not as a static, firm-specific variable, but as a dynamic, systemic propertythat propagates through inter-firm informational linkages and investor sentimentnetworks. Our methodology synthesizes principles from complex systems theory,behavioral finance, and textual analysis of unstructured disclosure data, movingbeyond traditional quantitative metrics of disclosure volume or frequency. We formulate and test three primary research questions: First, how do qualitative attributes of narrative disclosures—specifically semantic coherence, forward-lookingstatement density, and risk discussion granularity—influence the rate of asymmetrydecay in a market network? Second, what is the role of disclosure timing heterogeneity across a sector in either amplifying or dampening systemic informationasymmetry? Third, can a firm’s high-quality disclosure generate positive externalities by reducing asymmetry for peer firms with lower disclosure quality? Ouranalysis utilizes a unique, hand-collected dataset of annual report narratives fromthe industrial sector over a fifteen-year period, processed through a bespoke naturallanguage processing pipeline to extract the proposed qualitative dimensions. Results from our network contagion simulations reveal several non-intuitive findings.We demonstrate that the marginal impact of disclosure quality on asymmetry reduction is highly non-linear and contingent on a firm’s position within the sectoralinformation network. Firms acting as ’informational hubs’ exert a disproportionately large influence on systemic asymmetry. Furthermore, we identify a criticalthreshold of semantic coherence in narrative disclosures; beyond this threshold, thecontagion of reduced asymmetry accelerates significantly. We also find evidenceof strong positive externalities, where high-quality disclosures from market leadersmeasurably improve the informational environment for laggards, challenging thepurely competitive view of disclosure. The paper concludes by outlining the implications of this systemic, network-oriented perspective for regulators aiming toenhance market efficiency and for corporate managers strategizing their communication policies in an interconnected market ecology